Analysis of the scientific production of the Spanish Software Engineering Community - Burgueño-Caballero, Lola; Delgado-Moreno, Antonio; Vallecillo-Moreno, Antonio Jesús (My University, 2015)
Our group has been working on a report for the Spanish Society of Software Engineering and Software Development Technologies (SISTEDES) to provide a general overview of the Spanish scientific production and its contributions worldwide in the field of Software Engineering. Although a Database solution could have been used, we decided to employ Model-Driven Development (MDD) techniques in order to evaluate their applicability, suitability and fitness for these kinds of purposes, and to learn from the experience in this domain, which combines data integration, large scale models, and complex queries.
Keywords: Ingeniería del software - Investigación; SISTEDES; Spain; MDD; Scientific contribution; Software engineering